Effects of Virtual Reality in Patients Undergoing Dialysis: Study Protocol. Issue 6 (November 2019) - Burrai, Francesco; Othman, Shokri; Brioni, Elena; Micheluzzi, Valentina; Luppi, Marco; Apuzzo, Luigi; Delli Zotti, Giulia Bruna; La Manna, Gaetano
Abstract : Dialysis is often considered slow, repetitive, and with programmed intervals. Patients often perceive it as time taken from their lives with a sense of ineluctability and emptiness, engendering a negative emotional and cognitive perception of the world and one's place in it. Today, it is possible to improve the quality of life of patients during hemodialysis using virtual reality (VR). This creation of a true multisensory experience may absorb the patient's perceptions during hemodialysis, improving his/her quality of life. An Italian multicenter, longitudinal experimental study will be conducted with a randomized, pre-post test design, with balanced allocation 1:1, in parallel groups with a control group in the standard care of patients diagnosed with chronic renal failure who are, undergoing hemodialysis treatment. A sample of 186 patients calculated with sample size (power = 80%, β = 0.2, α = 0.05) will be randomized into an experimental group exposed to VR, and a control group in standard care. The 2 groups will be studied over a period of 1 month, with 12 applications of VR and with measurements of the following outcomes: anxiety, fatigue, pruritus, arterial pressure, heart rate, respiration rate, and duration of the session at each hemodialysis session. This is the first international experimental protocol that examines the application of VR in patients undergoing hemodialysis. If the results show statistically and clinically significant differences, the VR could be an additional holistic intervention, which is evidence based, linked to the humanization of chronic, repetitive interventions, complementary to and synergistic with standard of care.